The Influence of Work Environment, And Workload on Employee Turnover PT Parastar Distrindo Branch Office Sulawesi Tenggara - Yuana, Indira (International Journal of Management and Education in Human Development, 2024)
This study aims to determine the Influence of Work Environment, Compensation, and Workload on Employee Turnover Intention of PT Parastar Distrindo Branch Office Southeast Sulawesi. The type of research used is a quantitative approach. Data were collected using Observation, Questionnaire and Documentation methods. The data analysis technique used is the Multiple liniear regression test. The results of this study show that the Work Environment, Compensation, and Workload simultaneously affect the Employee Turnover Intention of PT Parastar Distrindo Branch Office Southeast Sulawesi. The Work Environment partially affects the Employee Turnover Intention of PT Parastar Distrindo Branch Office Southeast Sulawesi. Compensation partially affects the Employee Turnover Intention of PT Parastar Distrindo Branch Office Southeast Sulawesi. Workload Partially Affects Employee Turnover Intention of PT Parastar Distrindo Branch Office Southeast Sulawesi.